Analysis of the effects of migrant remittances on labor productivity in Burkina Faso: evidence from linear ARDL and non-linear ARDL approaches - Abdoul Hadirou Yoda; Achille Augustin Diendere (Cogent Economics & Finance)
This research aims to analyze the effects of migrant remittances on labor productivity in Burkina Faso over the period 1990–2022. This research contributes to the economic literature by examining the role of economic factors such as human capital and physical capital in analyzing the relationship between migrant remittances and labor productivity. Methodologically, the present research favors the use of linear ARDL and non-linear ARDL techniques to address the positive and negative changes of migrant remittances on labor productivity. Using the ARDL model, the results indicate that in the long run, remittances have an insignificant direct effect on labor productivity. These results are confirmed by the nonlinear ARDL model which shows that positive and negative changes in migrant remittances have no significant effect on labor productivity in Burkina Faso. Furthermore, the results show that internal economic factors such as human capital and physical capital amplify the positive effects of migrant remittances on labor productivity, suggesting spillover effects and positive externalities between these three variables. These results underline the need to recognize the potential of migrant remittances as important capital for financing development, by considering human and physical capital as channels influencing the dynamics of labor productivity.